DIFFERENCE IN THE DISTRIBUTION OF SELECTED BLOOD VARIABLES AMONG ATHLETES DURING A COMPETITION PERIOD - Sam Mugandani; Trayana Djarova-Daniels (Journal of Applied Sports Sciences)
Exercise is known to cause considerable changes in leucocyte counts and functions. The aim of the present study was to investigate the effect of exercise on leukocyte counts in athletes of different sporting codes during the competition time of the season. Forty-two university athletes voluntarily participated in the study, rugby players, male soccer players, female soccer players and female netball players. Blood samples were collected and analysis for whole blood count was done in Lancet laboratory, Richards Bay, RSA. Data were analyzed using unpaired t-test for treatment independent samples. It is noteworthy to point out the higher levels of leucocytes in the netball players than in female soccer players (6.8 ± 1.24 X 109 /L and 6.11 ± 1.28 X 109 /L respectively). The lymphocyte levels were also higher in the netball players than in female soccer players (2.60 ± 0.58 X109 /L and 2.16 ± 0.49 X109 /L respectively). There were also higher levels of leucocytes in the male soccer players compared to the male rugby players (6.26 ± 1.97X109 /L and 5.46 ± 0.99 X109 /L respectively). The lymphocyte levels were higher in the soccer players than in the rugby players (2.17 ± 0.36 X109 /L and 1.85 ± 0.32 X109 /L respectively), but the differences were not significant at p< 0.05. The changes in leucocytes could be a result (among other things) of the removal of dead cells related to exercise stress and trauma. It was expected, considering the levels of physical contact, that the leucocyte counts and the lymphocytes in particular were going to be higher among female netball players and male soccer players. The athletes’ results for the measured blood parameters were within the health norms. These findings could be related to the less intensive training protocols and lower levels of physical contact and stress in players from the students teams compared to the professional players